Lehrverantwortung – lutherisch / Doctrinal Responsibility – a Lutheran Perspective: Eine Studie des Ökumenischen Studienausschusses des Deutschen Nationalkomitees des Lutherischen Weltbundes / A Study by the Ecumenical Study Committee of the German National Committee of the Lutheran World Federation - Oberdorfer, Bernd,; Schuegraf, Oliver, (Evangelische Verlagsanstalt, 2023)
[Doctrinal Responsibility – a Lutheran Perspective] What does »doctrine« mean in Lutheran churches? What is it based upon? How is it made binding? What instances and processes of doctrinal judgment have developed? Who can decide doctrinal questions and how? This study first presents current structures of doctrinal understanding in German Lutheranism and unfolds exemplary historical case studies of Lutheran doctrinal responsibility (Bultmann controversy; ordination of women; apartheid; doctrine of justification). A second part outlines the emergence of Lutheran doctrinal and confessional norms in the 16th century and traces the development of concepts of ecclesial doctrinal commitment in a historical cross-section up to the present. Concluding theses explore the relevance of Lutheran doctrinal responsibility for ecumenical dialogues.